2020
DOI: 10.1108/ijlma-08-2017-0197
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of corporate social responsibility (CSR) and its implications on company value as a result of the impact of corporate governance and profitability

Abstract: Purpose The purpose of this study is to examine the effect of corporate governance and corporate profitability on firm value with corporate social responsibility (CSR) disclosure as the intervening variable. Design/methodology/approach The population of this study was all companies listed in the LQ 45 Index group in the Indonesia Stock Exchange in 2013-2014. The inferential statistics used in this study applied the partial least square (PLS) based structural equation model (SEM) method with the assistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 13 publications
4
45
0
19
Order By: Relevance
“…Various studies have found that CG elements, including the size of the board of directors [9], [10], [11], independent directors [11], [12], [13], and audit committee [14], [15], are determinants that have positive effect on sustainable disclosure. However, other researches find no effect [16], [17].…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…Various studies have found that CG elements, including the size of the board of directors [9], [10], [11], independent directors [11], [12], [13], and audit committee [14], [15], are determinants that have positive effect on sustainable disclosure. However, other researches find no effect [16], [17].…”
Section: Figurementioning
confidence: 89%
“…Banks' actions can have a major impact on society in general, and public demand for banks has both "ethics" and "values" (i.e. environmentally friendly banking practices) [16]. With deregulation and reduced state power in favor of the economy, there is expectation that banks should not only enjoy deregulation rights but also have an obligation for the interests of stakeholders by maintaining a balance between nature, social, and economy [18].…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Menurut [34], hasil penelitiannya menunjukkan bahwa tata kelola perusahaan dapat berdampak pada nilai perusahaan secara langsung. Hasil lainnya menyatakan tidak ada peran pengungkapan CSR dalam memediasi efek tata kelola perusahaan terhadap nilai perusahaan.…”
Section: Laporan Keberlanjutan: Penghindaran Pajak Dan Nilai Perusahaanunclassified
“…This distinguishes it from previous studies done on the influence of GCG, CSR, and tax avoidance on value creation that were partial. The results of a study conducted by Mangoting et al, (2019), Kamaliah (2020) deduced that the CSR disclosure of a company could not mediate the relationship between GCG and value creation. This is because CSR disclosure incurs a high cost for the company, so directors and commissioners usually do not mandate it, instead making CSR a voluntary activity.…”
Section: Introductionmentioning
confidence: 99%